Organic‐Free Synthesis of Silicoaluminophosphate Molecular Sieves. (26th June 2018) - Park, Sung Hwan; Choi, Wanuk; Choi, Hyun June; Hong, Suk Bong
Abstract: Silicoaluminophosphate (SAPO) molecular sieves are an important class of microporous materials and are useful for industrial catalysis and separations. They have been synthesized exclusively by the use of expensive and environmentally unfriendly organic structure‐directing agents. Now the synthesis of SAPO molecular sieves is reported with MER, EDI, GIS, and ANA topologies under wholly inorganic conditions. Multinuclear MAS NMR analyses demonstrate the presence of Si, Al, and P atoms in their frameworks. These SAPO materials all have unusually high framework charge densities (0.25–0.46), owing to the small size of alkali metal cations used as an inorganic structure‐directing agent. A continuous Si increase in the synthesis gel for MER‐type SAPO molecular sieves led to the formation of framework Si(0Al) units, decreasing the number of extra‐framework cations per unit cell and thus making the resulting solid useful for CO2 adsorption.